Evaluation of mHealth Applications Security Based on Application Permissions. - PUSTOZEROV, Evgenii; VON JAN, Ute; ALBRECHT, Urs-Vito (Studies in Health Technology & Informatics, 2016)
The presented study covers the evaluation of ratings of a set of 1080 applications classified as “top apps” for the two categories “Medicine” and “Health & Fitness” as they are available on Google’s Play Store. Within the evaluation, the manifest files and source code of the applications were analyzed in order to reveal whether the requested set of permissions correspond to the ones really utilized by the apps and whether they surpass what is necessary. For many apps, the declarations in the manifest file do not match what is specified in the source code, raising the question of whether this may be an indication of questionable app quality with a potentially negative impact on the safety and reliability of mHealth related apps.